"Protrusions" or "holes" in graphene: which is the better choice for sodium ion storage?12. Issue 4 (30th March 2017) - Yang, Yijun; Tang, Dai-Ming; Zhang, Chao; Zhang, Yihui; Liang, Qifeng; Chen, Shimou; Weng, Qunhong; Zhou, Min; Xue, Yanming; Liu, Jiangwei; Wu, Jinghua; Cui, Qiu Hong; et al.
Abstract : The introduction of protrusions through P-doping into graphene is an effective strategy to enhance electrochemical performances in SIBs. Abstract : The main challenge associated with sodium-ion battery (SIB) anodes is a search for novel candidate materials with high capacity and excellent rate capability. The most commonly used and effective route for graphene-based anode design is the introduction of in-plane "hole" defects via nitrogen-doping; this creates a spacious reservoir for storing more energy. Inspired by mountains in nature, herein, we propose another way – the introduction of blistering in graphene instead of making "holes"; this facilitates adsorbing/inserting more Na + ions. In order to properly answer the key question: " "protrusions" or "holes" in graphene, which is better for sodium ion storage?", two types of anode materials with a similar doping level were designed: a phosphorus-doped graphene (GP, with protrusions) and a nitrogen-doped graphene (GN, with holes). As compared with GN, the GP anode perfectly satisfies all the desired criteria: it reveals an ultrahigh capacity (374 mA h g −1 after 120 cycles at 25 mA g −1 ) comparable to the best graphite anodes in a standard Li-ion battery (∼372 mA h g −1 ), and exhibits an excellent rate capability (210 mA h g −1 at 500 mA g −1 ). In situ transmission electron microscopy (TEM) experiments and density functional theory (DFT) calculations were utilized to uncover the origin of the enhanced electrochemical activity of "protrusions" compared to "holes" in SIBs, down to the atomic scale. The introduction of protrusions through P-doping into graphene is envisaged to be a novel effective way to enhance the capacity and rate performance of SIBs.